Effects of GLP-1 receptor agonists on arrhythmias and its subtypes in patients with type 2 diabetes: A systematic review and meta-analysis - Wei, Jinjing; Wang, Ruxin; Ye, Haowen; Wang, Ying; Wang, Lihong; Zhang, Xiaofang (Frontiers in Endocrinology, 2022)
Abstract Purpose An update of a systematic review and meta-analysis of the risk of arrhythmias and their subtypes in type 2 diabetic patients receiving glucagon-like peptide 1 receptor agonist (GLP-1RA) medication according to data from the Cardiovascular Outcome Trial（CVOT）。 Methods This meta-analysis was aligned with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines[1]，the protocol was registered in The International Prospective Register of Systematic Reviews (PROSPERO) under ( CRD42022315234)。Randomized controlled trials (RCT) on GLP-1RA therapy and cardiovascular outcomes in type 2 diabetes mellitus patients published in full-text journal databases such as MEDLINE (via PubMed), Embase, Clinical Trials.gov, and the Cochrane Library from establishment to March 1, 2022 were searched. We assessed the quality of individual studies by the Cochrane risk-of-bias algorithm. RevMan 5.4.1 software was use for calculating meta-analysis. Results Pooled analysis reported no significant effect on total arrhythmia [RR=0.96, 95% CI (0.96, 1.05), p =0.36] (Figure 2), and its subtypes such as atrial fibrillation [RR=0.96, 95% CI (0.86, 1.07), p =0.43] (Figure 3), atrial flutter [RR= 0.82, 95% CI (0.57, 1.19), p =0.30] (Figure 3), atrial tachycardia [RR=0.64, 95% CI (0.20, 2.01), p =0.44)] (Figure 3), sinoatrial node dysfunction [RR=0.74, 95% CI (0.44, 1.25), p =0.26] (Figure 3), ventricular preterm systole [RR=1.42, 95% CI (0.62, 3.26), p =0.41] (Figure 3), second degree AV block [RR=0.96, 95% CI (0.53, 1.72), p =0.88] (Figure 3) , complete AV block [RR=0.75, 95% CI (0.49, 1.17), p =0.21] ( Figure 3), ventricular fibrillation [RR=1.00, 95% CI (0.50, 2.02), p =1.00] (Figure 3), ventricular tachycardia [RR=1.37, 95% CI (0.91, 2.08), p =0.13] (Figure 3) from treatment with GLP-1RA versus placebo. However, the risk of hypoglycemia was reduced by about 30% [RR=0.70, 95% CI (0.57, 0.87), P=0.001] (Figure 4) and the risk of pneumonia by about 25% [RR=0.85, 95% CI (0.75, 0.97), P=0.01] (Figure5), both statistically significant differences. Conclusion In type 2 diabetic patients, treatment with GLP-1RA has no significant effect on the risk of major arrhythmias but significantly reduces the risk of hypoglycemia and pneumonia.